RELATIONSHIP OF WORK STATIONS ON MUSCULOSKELETAL COMPLAINTS AND WORK PRODUCTIVITY OF WORKERS IN MSMEs TEMPE CHIPS IN BLIMBING DISTRICS MALANG CITY - Wisynu Ari Gutama; Adinda Kusumaningdiah Tantri (Universitas Muhammadiyah Jember, 2019)
The application of ergonomics aspects needs to be considered by MSMEs because in this case MSMEs still apply the work process manually, so that the risks posed by the ergonomic aspects will also be greater. The lack of attention of these industry players to musculoskeletal complaints and occupational risk, this study was conducted with the aim of 1) Analyzing the assessment of work attitudes on workers using the Quick Exposure Checklist (QEC) method; 2) Analyzing the complaints of musculoskeletal workers at the MSMEs Tempe Chips Blimbing District, Malang City; and 3) Analyzing the relationship of work stations to musculoskeletal complaints and productivity of MSMEs Tempe Chips workers in Blimbing District, Malang City. In the assessment of work attitudes, 20 employees in the MSMEs Tempe Chips had an exposure level between 51-70% and needed further research actions and needed changes. Musculoskeletal complaints of MSMEs Tempe Chips workers in Belimbing District, Malang City mostly have a low level of 58.82% and body parts that are often complained by employees, namely shoulders, back and knees. The relationship of the work station to musculoskeletal complaints has a moderate level. The relationship of work stations to productivity and the relationship of musculoskeletal complaints with productivity has a very low value.